IMAGE MANAGEMENT STRATEGİES FOR MANAGERS (Third Sector Social Economic Review, 2014)
Image management is one of the most important topic with the organisational behaviour studies nowadays. This study aims at examining image management strategies for managers. Now the image could be evaluated both personal and organizational level. In particular, it is thought that image management strategies had important contribution to increase organizational effectiveness and efficiency for organizational field. Although individuals gain prestige in society by managing their personal images, enterprises increase their managerial effectiveness by managing their organizational image. Managers who support the image management strategies have to redesign their organisational structures by aligning with the image strategies. Executives must motivate their employees and managers for personal image management. This paper underlines the concept of image which will be made clear before in line with the basic these assumptions. Thus, the emergence of the image, its functions, types, image policy and transfer and brandimage will be examined in this study. Afterwards, image management, its process, personal and organizational image management and image management strategies will be discussed.
Keywords: Image; Image Management; Personal Image; Organizational Image; Effective Stance